DECENTRALISATIE WET VAN NEDERLAND INDIES 1903 - Teti Hestiliani (ISTORIA: Jurnal Pendidikan dan Sejarah, 2019)
AbstractAt the end of the 19th century there was a change in the system of government in the Dutch East Indies, before a central system was implemented in which all activities were regulated by the central government in Batavia. Then this becomes increasingly complex when various affairs in the region must become central business. The change in the system of government in the Indies was then noticed by various figures in the Dutch parliament and government officials in the Dutch East Indies. This change in the system of government was also an effort to improve the standard of living in the Indies which was considered no longer a wingewest area. then in 1901 through his speech Ratu Wilhelmina conveyed that there must be a change in the system of government in the Indies. Then in 1903 a decentralization law was issued as the basis for regional autonomy in the Dutch EastIndies.  Keywords: Decentralization, Dutch East Indies, City